O papel do RNA longo não codificante H19 no desenvolvimento da síndrome mielodisplásica - Borges, Daniela de Paula (2022)
H19 is a long noncoding RNA (lncRNA) expressed only from the maternal allele by imprinting. H19 transcription is controlled by the Imprinting Control Region (ICR) of the Differentially Methylated Region (DMR) H19DMR mediated by the protein CTCF. H19 regulates several physiological functions and can act both as an oncogene and tumor suppressor in many neoplasias, suggesting a promising target for therapies, especially in very heterogeneous diseases such as Myelodysplastic Syndrome (MDS). The main challenge in MDS has been the discovery of biomarkers to differentiate between mutations in normal hematopoietic progenitor cells and those that lead to neoplastic development, enabling the study of new specific target drugs that increase patient survival. In this study, we evaluated the expression levels of H19, by RT-qPCR, the methylation pattern of the H19DMR region by DNA sequencing technique after modification with sodium bisulfite, and protein expression of CTCF by immunohistochemistry, in 70 patients with SMD classically considered as lowrisk (SMD with ring sideroblast/SF3B1 mutation - SMD-RS), high-risk (SMD with excess blasts - SMD-EB), 11 patients with AML secondary to SMD (AML sec) and 8 healthy controls. We identified increased H19 expression levels in the healthy control group compared to the SMD-RS patients (p=0.004), in addition to increased expression in the SMDRS group compared to the SMD-EB (p=0.006) and AML sec (p=0.049) groups. Patients with AML sec showed increased methylation of the H19DMR region (p=0.022), which was also observed in MDS patients older than 60 years (p=0.031). Increased H19 expression was found in individuals aged less than 60 years (p=0.614), normal karyotype (p=0.003), and platelet count higher than 100,000/mm³ (p=0.019), both associated with good prognosis in MDS. Patients with MDS and increased H19 expression had longer overall survival (p=0.379). The results suggest an association of H19 expression with a more favorable clinical presentation for MDS with an increase of its methylation in the evolution of the disease, possibly functioning as a tumor suppressor gene for Myelodysplastic Syndrome, an extremely heterogeneous disease.